Trajectory generation for road vehicle obstacle avoidance using convex optimization - Bevan, G P; Gollee, H; O'Reilly, J (Proceedings of the Institution of Mechanical Engineers. Part D, Journal of automobile engineering, 2010)
Abstract This paper presents a method for trajectory generation using convex optimization to find a feasible, obstacle-free path for a road vehicle. Consideration of vehicle rotation is shown to be necessary if the trajectory is to avoid obstacles specified in a fixed Earth axis system. The paper establishes that, despite the presence of significant non-linearities, it is possible to articulate the obstacle avoidance problem in a tractable convex form using multiple optimization passes. Finally, it is shown by simulation that an optimal trajectory that accounts for the vehicle's changing velocity throughout the manoeuvre is superior to a previous analytical method that assumes constant speed.